„New Landscapes” by closed matter cycles: Which landscapes do we need in central Europe for the next century? - Hildmann, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Sustainable development of landscape as material basis of society is determined by two limitations: minimisation of high irreversible losses of base cations and nutrients and the increasing need to use regenerative energy sources. Twelve management rules are derived. There are specified by suggested management modules. Chances to realise a sustainable development result from changing frame conditions for the land cultivators (farmers and foresters). Thereupon the role of planning should be changed.
Keywords: Article